2022
DOI: 10.3389/fphys.2022.890102
|View full text |Cite
|
Sign up to set email alerts
|

Myosin 5a in the Urinary Bladder: Localization, Splice Variant Expression, and Functional Role in Neurotransmission

Abstract: Dysregulation of neurotransmission is a feature of several prevalent lower urinary tract conditions, but the mechanisms regulating neurotransmitter release in the bladder are not completely understood. The unconventional motor protein, Myosin 5a, transports neurotransmitter-containing synaptic vesicles along actin fibers towards the varicosity membrane, tethering them at the active zone prior to reception of a nerve impulse. Our previous studies indicated that Myosin 5a is expressed and functionally relevant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Our analysis indicated that variant ACEF was not abundantly expressed in pelvic tissues, although its presence can be inferred in distal colon by a degree of resistance of the ∼600 bp fragment to Ban II digestion, and its presence was inferred as a minor species in bladder ( Carew et al, 2022 ). In contrast, the ∼600 bp fragment from bladder and CCP was extensively cleaved by Ban II, suggesting it was comprised mostly of ACDE in these tissues.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Our analysis indicated that variant ACEF was not abundantly expressed in pelvic tissues, although its presence can be inferred in distal colon by a degree of resistance of the ∼600 bp fragment to Ban II digestion, and its presence was inferred as a minor species in bladder ( Carew et al, 2022 ). In contrast, the ∼600 bp fragment from bladder and CCP was extensively cleaved by Ban II, suggesting it was comprised mostly of ACDE in these tissues.…”
Section: Discussionmentioning
confidence: 78%
“…The ABCE variant of Myo5a is so abundantly expressed in neurons of the central nervous system that it is referred to as the brain form and might be expected to be the most prevalent form in the peripheral nervous system as well. However, our previous work implied that this was not the case: the ABCE variant is detectable in stomach sections but undetectable in bladder, while variants containing the alternative exons D and F were identified in both tissues ( Carew et al, 2021 ; Carew et al, 2022 ). Based on immunohistochemistry data, Myo5a protein is found predominantly in nerve trunks and extensions where it colocalizes with axonal markers such as synaptophysin and β-III-tubulin.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations